Gamification – The power of motivation using Octalysis Framework - Matos, Pedro Frazão (2019)
In the context where the strong technology advance transforming patterns and creating new obstacles, the capacity for the companies to innovate represents a competitive advantage. In this real-time world to have innovation, companies need dedicated employees fully engaged and it is used in organizations in order to change the behavior of the workforce as well to engage and make them more effective. This work aims at analyzing the effectiveness of the gamification process in the present day scenario. Special focus lies on answering the leading question whether and when gamification can be used as a tool for motivation. Thus, the present work aims to find the applicability of gamification in the enterprise context with the help of octalysis framework. It also gives a clear understanding on the concepts of gamification and gives an in-depth review on all the elements such as mechanics, design, etc. that go into it and the measures of the effectiveness of the process with the help of various frameworks and studies that have already been done. To achieve this goal it was performed an exploratory scientific journey using the techniques of bibliographic reviews and content analysis, in order to develop a small prototype using gamification. By reviewing the literature, recommendations and conclusions are drawn that would help understand how to make the gamification process effective in the present day scenario and also gives insights into future of gamification. For future work, as research continues, an empirical research is proposed.